Sikap Gereja Terhadap Bahaya Neoliberalisme Kebijakan Masyarakat Ekonomi Asean Dalam Konteks Negara Kesatuan Republik Indonesia - Keristian Dahurandi (Jurnal Alternatif Wacana Ilmiah Interkultural, 2017)
The ASEAN Economic Community (MEA) is an ASEAN regional policy to establish market integration. To make this happen the government must minimize the market mechanism for the market to run freely and naturally. Consequently, in the MEA policy of the State institution which in this case the government is represented is tested because this policy may pose a danger to neoliberalism. Nevertheless, this policy is the only last resort to face global market expansion. The Church as a part of people’s life also retains the main attitude of rejecting all forms of colonialization or defamation of human dignity. A member of the Church is required to have an “added” value as a form of the ability to read the “signs of the times” in evangelization and the development of the life of faith. In the context of the MEA’s policy, members of the Church must be competitive- covenant, economical-subsidiary, adaptive-prophetic, and participatory- eschatological.